The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s11999-008-0288-2
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of ACL Allografts is Inhibited by Peracetic Acid Sterilization

Abstract: Sterilization of allografts for anterior cruciate ligament (ACL) reconstruction has become an important prerequisite to prevent disease transmission. However, current sterilization techniques impair the biological or mechanical properties of such treated grafts. Peracetic acid (PAA) has been successfully used to sterilize bone allografts without these disadvantages and does not impair the mechanical properties of soft tissue grafts in vitro. We asked whether PAA sterilization would influence recellularization,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 32 publications
3
25
0
1
Order By: Relevance
“…37,38 Analyses of the mechanical function of BPTB grafts in vitro revealed no adverse effects of PAA sterilization compared with unsterilized grafts. 39 A more recent study, 40 however, found in a goat model that PAA sterilization delayed or partially inhibited the biological remodeling of PAA grafts, leading to impaired functional knee stability and reduced structural properties of the graft during subsequent healing up to 3 months. The authors recommend caution when considering PAA-sterilized allografts for ACL reconstruction.…”
Section: Disinfection and Secondary Sterilizationmentioning
confidence: 99%
“…37,38 Analyses of the mechanical function of BPTB grafts in vitro revealed no adverse effects of PAA sterilization compared with unsterilized grafts. 39 A more recent study, 40 however, found in a goat model that PAA sterilization delayed or partially inhibited the biological remodeling of PAA grafts, leading to impaired functional knee stability and reduced structural properties of the graft during subsequent healing up to 3 months. The authors recommend caution when considering PAA-sterilized allografts for ACL reconstruction.…”
Section: Disinfection and Secondary Sterilizationmentioning
confidence: 99%
“…39,40 Other authors have also encouraged caution with the continued widespread use of peracetic acid, which may further inhibit graft incorporation in animal models. 41 Continued clinical surveillance and US Food and Drug Administration scrutiny of current sterilization practices used by the American Association of Tissue Banks are warranted, particularly with increased use of musculoskeletal allograft tissue in current orthopaedic practice. Although debate exists, the current literature shows a trend toward a longer remodeling period and delayed biologic healing in allograft tissue when compared with autografts, [42][43][44] possibly up to 2 years or more after surgery.…”
Section: Studymentioning
confidence: 99%
“…Several studies have demonstrated the antimicrobial efficacy of this method. Although the peracetic acid treatment is an established sterilization method of bone, dermis and amniotic membrane transplants with no evidence to impair the transplants properties, it has caused significantly reduced biomechanical strength and decreased remodeling activity in anterior cruciate ligament reconstruction tendon grafts [35] . Chemical processing and antibiotic soaks have certain limitations for sterilization of allograft tissues due to the lack of complete penetration for inactivation of deep-seated bioburden.…”
Section: Methods For Sterilization Of Tissue Allograftsmentioning
confidence: 99%